2017
DOI: 10.1038/srep42032
|View full text |Cite
|
Sign up to set email alerts
|

Microbial nitrification, denitrification and respiration in the leached cinnamon soil of the upper basin of Miyun Reservoir

Abstract: Leached cinnamon soil is the main agricultural soil distributed in the North China Plain. In this research, leached cinnamon soil samples were collected in the upper basin of Miyun Reservoir (northeast of Beijing, China). The BaPS method (Barometric Process Separation) was applied to measure nitrification, denitrification and respiration rates. The rates of nitrification, denitrification and respiration were 0–120.35 μg N/kg SDW h, 0–246.86 μg N/kg SDW h and 0.17–225.85 μg C/kg SDW h (Soil Dry Weight, SDW), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
7
1
Order By: Relevance
“…Lower Rs under higher available N or N mineralization was usually attributed to lower heterotrophic respiration and microbial activity, whereas the higher Rs were generally found in N-limited ecosystems [15,16]. In contrast to other N-saturated ecosystems [12], our study showed that Rs positively correlated with R N and R M ( Figure 5).…”
Section: Soil Respiration In Response To Incremental N Gradientscontrasting
confidence: 43%
See 1 more Smart Citation
“…Lower Rs under higher available N or N mineralization was usually attributed to lower heterotrophic respiration and microbial activity, whereas the higher Rs were generally found in N-limited ecosystems [15,16]. In contrast to other N-saturated ecosystems [12], our study showed that Rs positively correlated with R N and R M ( Figure 5).…”
Section: Soil Respiration In Response To Incremental N Gradientscontrasting
confidence: 43%
“…Soil respiration (Rs), an essential component of the C cycle, is the primary pathway of carbon dioxide (CO 2 ) flux from soil to atmosphere [11]. As the increasing concern about the effects of globally reactive N deposition on Rs [12], the responses of Rs to the altered N status remain controversial [13] and could either increase [14,15], decrease [12,16], or not change [17,18] in different terrestrial ecosystems. In forests, one possible reason for the highly variable response of Rs is mainly attributed to background soil N status before N addition.…”
Section: Introductionmentioning
confidence: 99%
“…Herbivore manure is important in grassland nutrient cycling; however, intensified livestock production can lead to excess manure. Deposition of this waste can contaminate groundwater and increase nitrate and phosphate concentrations, causing soil hardening and/or salinization, negatively impacting soil physicochemical properties and soil microbial communities (Groenigen et al, 2005 ; Sun et al, 2015 ; Xu et al, 2017 ). To mitigate these issues, manure can be processed into organic fertilizer via composting (Moral et al, 2009 ; Tang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, soil microbial biomass measurements are important in ascertaining the extent of chemical stress and/or disturbance on soil ecosystem and the time dependence of microbial recovery. Most studies have used respiration rate (Fournier et al, 1992;Nakamoto and Wakahara, 2004;Anyanwu and Semple, 2016a;Sun et al, 2017;Xu et al, 2017) and changes in biomass (Anyanwu and Semple, 2016a;Mehnaz et al, 2017;Siles and Margesin, 2017).…”
Section: Introductionmentioning
confidence: 99%